Analisis Daya Saing UMKM Barbershop di Kota Palembang - Yohanes Dicka Pratama; Johan Gunady Ony (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2020)
In Palembang, the Barbershop industry is growing very rapidly. Barbershop in Palembang City is one of the Micro, Small and Medium Enterprises (MSMEs) in the service sector. Currently there is no clear data regarding the development of the barbershop business. However, it is clear that it is clear that the growth of this business will have a positive impact on improving the welfare of the people in Palembang City. As a business that is still classified as an MSME, barbershop is faced with various challenges. From minimal management to access to capital. There is not much research on this type of business, so data on challenges and obstacles is not yet available. From some data, there are several well-known barbershop in Palembang, namely Big Daddy's Barbershop and F1 Barbershop. Both barbershop are quite busy with customers every day. Even so, there are several barbershop in Palembang City that have to roll over. In general, this barbershop business has increased significantly every year. With the increasing interest and lifestyle of the people of Palembang, this business has considerable potential. What is done in this research is to map the MSME barbershop based on the level of competitiveness. Competitiveness is one measure of the sustainability of a business. With high competitiveness, a business can provide services according to customer expectations. The results of MSME mapping based on competitiveness can be used as the basis for policies or business development strategies. In order to achieve the research objectives, this study went through three stages. The first stage is the measurement of competitiveness. The competitiveness indicator used is profit and also the number of services. The second stage is mapping. The mapping method used is K-Means. This method is used because it is simple and the researcher can determine the number of clusters desired. In this research, two clusters will be made. The consideration taken is that this barbershop business is not too high heterogeneity between one business and another, so if too many clusters are formed it will be ineffective. The last step to take is analysis of each cluster. From the results of data processing obtained two clusters, namely the TOP cluster and the ordinary cluster. The TOP cluster is a collection of barbershop that has a good level of competitiveness, while the regular cluster is a barbershop that has low competitiveness.